ANTI-INFLAMMATORY EFFECT OF PLANTAGO SP ETHANOLIC EXTRACT IN MURINE RAW264.7 MACROPHAGE CELLS - Ay, N V; Kh, Altantsetseg; V, Enkhchimeg; O, Baatartsogt (Mongolian Journal of Agricultural Sciences, 2018)
Besides being recorded as a traditional medicine, nowadays, plantain plants (Plantago sp.) are appreciated in many more aspects. Plantain is a name applied both to a drug and to a vegetable in a number of countries as Vietnam, China, Cambodia, Laos and North American Indians [9, 13]. Plantago sp. traditionally used for treating wound, fever and inflammation in Asia. This study aimed to investigate the anti-inflammatory activity of ethanolic extracts of Plantago sp. including P. major L. and P. depressa Willd. on RAW 264.7 murine macrophage cells. Cells were treated with different concentration of the PAE extract (50, 100, 200, 400 μg/mL) with or without lipopolysaccharide (LPS) stimulation to evaluate its effect on cell viability, using CCK-8 assay. Nitric oxide (NO) production was assessed by Griess reagent on LPS-stimulated cells using preceding PEE treatment. Furthermore, mRNA expression of inflammmatory-related genes were evaluated by RT-PCR analysis. The results revealed that PEE treatment increased cell viability in naive cells whereas inhibited cell profileration in LPS-stimulated cell dose-dependently. In addition, NO emission and mRNA level of IL-1β, IL-6, iNOS, COX-2 and NF-κB decreased by dose dependant manner. As summary, PEE exhibits anti-inflammatory activity through inhibition of pro-inflammatory mediators mRNA expression in macrophages.